The Influence of Perceived Security, Ease of Use, Promotion, and Trust on the Intention to Use Digital Payments in Karanganyar’s Conventional Stores - Adellia Bella Yuda Slankiza; Titin Hargyatni (LPPM Politeknik Pratama, 2025)
This study explores the factors influencing consumer decisions to use digital payments in conventional stores. As digitalization grows in the retail sector, understanding the key drivers and barriers of adoption becomes essential. Using a quantitative approach, data were collected via surveys from 100 respondents across urban and rural areas in Indonesia. To minimize bias, both online (Google Forms) and offline (printed) questionnaires were used to ensure inclusion of digitally inexperienced respondents. The variables analyzed include perceived security, ease of use, promotional strategies, and trust. The multiple linear regression analysis showed that all four variables positively and significantly influenced adoption. The comparison between urban and rural users highlighted digital divide issues, emphasizing the need for tailored strategies to support adoption in underserved areas.